Gambaran Prevalensi Hipertensi dan Faktor Risiko Utama di Indonesia – Analisis Data Tingkat Kabupaten/Kota: Overview of Hypertension Prevalence and Its Main Risk Factors in Indonesia – a District-Level Data Analysis - Wahidin, Mugi; Mustikawati, Intan Silviana; Handayani, Rini; Letelay, Alfons M. (Amerta Nutrition, 2025)
Background: Hypertension is one of the serious health problems in Indonesia with a prevalence of 34.1%. Specific risk factors including an unhealthy diet might influence the disease. Objectives: The study aimed to describe the prevalence of hypertension, difference in the prevalence across districts/cities and regions, and analyze the main risk factors of the disease at district level in Indonesia. Methods: This cross-sectional is a descriptive secondary data analysis of Basic Health Research 2018 using mean comparison, correlation, and multivariate linear regression analysis. The analysis incorporated aggregate data from 478 districts. The dependent variable was hypertension prevalence, and the independent variables were obesity, central obesity, smoking, salty, instant, and fatty food consumption, fruit and vegetable consumption, physical activity, and blood pressure check. The sampling technique was total sampling with criteria of all variables having complete data. Results: The mean prevalence of hypertension in districts in Indonesia was 31.18%. There was no difference in hypertension prevalence between districts and cities but there was a difference across seven regions in Indonesia, namely Sumatera, Java-Bali, Nusa Tenggara, Kalimantan, Sulawesi, Maluku, and Papua. The most influential risk factors were regular blood pressure checks (Beta 0.326), lack of fruit and vegetable consumption (Beta 0.169), salty foods consumption (Beta 0.124), and fatty foods consumption (Beta 0.055). Conclusions: Blood pressure checks and an unhealthy diet were the most influential risk factors for hypertension. It is recommended for the Government and the public to increase blood pressure screening and avoid unhealthy diets.